Simbol Dan Makna Tari Langga Buwa Karya Muraji Bereki - Nurlia Djafar (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
ABSTRACT The purpose of this study was to analyze the symbols and meanings contained in Muraji Bereki's Langga Buwa dance. This research method is qualitative by examining every symbol in dance that is influenced by the social system with the various cultures that surround it. The results of the research are the symbols and meanings of the Langga Buwa dance that are displayed through movement, dancers and others that have a relationship with concepts, general ideas, patterns and shapes that give rise to symbols involving denotative and connotative meanings. The conclusion of this research is that the analysis of Langga Buwa dance performances reflects gender equality which wants to show the existence of women in fulfilling their rights so that they are equal to men. Gender differences are only in gender, while the attitudes and characteristics of each are something that can be exchanged, so that men and women should receive equal treatment both their rights and obligations in social life. Keywords: Gender, Langga Buwa, Langga/Longgo.